Shear performance of high-strength bolt connector considering different pad and bolt hole. (December 2020) - Zhao, Wei; Lu, Senqiang; Jing, Xiuying
Abstract: Better than traditional stud connectors, the high-strength bolts enable rapid assembly of steel–concrete composite beams and replacement of decks. However, the researches on the shear performance of high-strength bolt connectors in prefabricated steel–concrete composite beams are relatively limited. Existing studies have not considered the effect of bolt holes in concrete slabs on structural performance. In this paper, the shear performance of high-strength bolt connector of prefabricated steel–concrete composite beams was investigated. The shear bearing capacity, shear stiffness and failure mode were obtained by push-out test. The impact of different bolt hole diameters and pad sizes were considered. Bolt hole diameter of 24 mm, 28 mm and 32 mm, pad size of 50 mm × 50 mm, 80 mm × 80 mm, 200 mm × 100 mm were used in the push-out tests. The results showed that all the specimens were damaged due to crushing of concrete along with shear deformation of bolts. Increasing the pad size can effectively reduce the cracking of concrete slab and improve the slip load and post-slip shear stiffness of specimens. The slip load and peak load of specimens are mainly dependent on the diameter of bolt hole. Specimens with small bolt hole achieve significantly higher pre-slip and post-slip shear stiffness compared to specimens with large bolt hole diameter.